2003
DOI: 10.1002/elan.200390064
|View full text |Cite
|
Sign up to set email alerts
|

Permselective Properties of Electropolymerized Guaiacol Derivatives

Abstract: Guaiacol (2-methoxyphenol) and its 5 derivatives such as 4-allyl-2-methoxyphenol,2-methoxy-4-propenylphenol, 2-methoxy-4-propylphenol, 4-hydroxy-3-methoxybenzylamine and 4-chloro-2-methoxyphenol were oxidatively polymerized on platinum electrodes in 0.1 M NaOH solution. The polymer modified electrodes were then checked for their responses towards biologically important analytes such as hydrogen peroxide, ascorbic and uric acids, dopamine and acetaminophen under flow injection conditions. The effect of a monome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
13
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 13 publications
0
13
0
Order By: Relevance
“…In the aqueous system, the oxidation broad peak was observed at a potential of 300 to 500 mV (vs. Ag/AgCl electrode) in the first cycle. However, no peaks were observed when repeating the cycle more than two times; this phenomenon has been observed in the case of many other phenolics Kirk 1993a, 1993b;Ciszewski and Milczarek 2001;Ezerskis and Jusis 2001;Milczarek and Ciszewski 2003;Ferreira et al 2006). During electrooxidation, many phenolic compounds in an aqueous medium undergo rapid film passivation on the electrode surface, leading to a drastic decrease in the current, whereas in an organic solvent medium, the oxidation peaks are observed at ~800 mV after repeating the cycle more than twice.…”
Section: Analysis Of the Solution After Electropolymerizationmentioning
confidence: 79%
“…In the aqueous system, the oxidation broad peak was observed at a potential of 300 to 500 mV (vs. Ag/AgCl electrode) in the first cycle. However, no peaks were observed when repeating the cycle more than two times; this phenomenon has been observed in the case of many other phenolics Kirk 1993a, 1993b;Ciszewski and Milczarek 2001;Ezerskis and Jusis 2001;Milczarek and Ciszewski 2003;Ferreira et al 2006). During electrooxidation, many phenolic compounds in an aqueous medium undergo rapid film passivation on the electrode surface, leading to a drastic decrease in the current, whereas in an organic solvent medium, the oxidation peaks are observed at ~800 mV after repeating the cycle more than twice.…”
Section: Analysis Of the Solution After Electropolymerizationmentioning
confidence: 79%
“…It has to be emphasized that in earlier studies reversible redox activity was only observed for immobilised compounds [19][20][21], whereas in solution only irreversible oxidation was reported [18,20]. This is connected with the formation of non-electroactive dimers and/or polymers [17,18,20].…”
Section: Electrochemical Characterisation Of Electrodesmentioning
confidence: 83%
“…This may be caused by the formation of a nonconducting polymer in the silicate matrix, blocking reactant access to the Au surface. The oxidative electropolymerisation of various phenolic compounds resulting in nonconductive polymer formation has been reported previously [16][17][18][19][20][21].…”
Section: Electrochemical Characterisation Of Electrodesmentioning
confidence: 94%
“…In some cases, however, hydrophobic character of such films forces preferential uptake of hydrophobic analytes like DA coupled with the rejection of a hydrophilic compound like AA. A great enhancement in selectivity and sensitivity of the voltammetric quantification of DA has been shown for electropolymerized eugenol [29] and other guaiacol derivatives [41]. Hence, transport properties of electropolymerized phenols are governed both by film microstructure, i.e., its integrity, and by specific interactions with permitting molecules such as dipol -dipol or hydrophobic interactions.…”
Section: Electropolymerization Of Bahhfp On Glassymentioning
confidence: 98%